Keeping up with the kids: mobility patterns of young individuals from the St. Mary Magdalen Leprosy Hospital (Winchester) - Filipek-Ogden, K. L.; Roberts, Charlotte; Montgomery, Janet; Evans, Jane; Gowland, Rebecca; Tucker, Katie (American Journal of Physical Anthropology, 2025)
Leprosy is one of the few specific infectious diseases that can be studied in bioarchaeology due to its characteristic debilitating and disfiguring skeletal changes. Leprosy has been, and continues to be, one of the most socially stigmatising diseases in history, over-riding all other aspects of social identity for the sufferers and frequently resulting in social exclusion. This study examines the stable isotopic evidence of mobility patterns of children, adolescents, and young adult individuals with the lepromatous form of leprosy in Medieval England (10th –12 th centuries AD) to assess whether the individuals buried with the disease were non-locals, possibly from further afield. Enamel samples from 19 individuals from the St. Mary Magdalen Leprosy Hospital, Winchester (UK) were selected for strontium (87Sr/86Sr) and oxygen (d18O) radiogenic and stable isotope analysis based on age at death (<30 years), the presence of bone changes associated with lepromatous leprosy, and the underlying geology of their burial locations. The results from these data indicate that the St. Mary Magdalen Leprosy Hospital received an almost equal mixture of local and non-local individuals from further afield, including early pilgrims. At present, the St. Mary Magdalen Leprosy Hospital is the earliest dedicated leprosaria found within Britain and mobility studies such as these can help elucidate and test some of the broader historical notions and identities associated with the movements of those infected with the disease in Medieval England.